2019
DOI: 10.1111/bjd.18239
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma characterization using fusionex vivoconfocal microscopy: a promising change in conventional skin histopathology

Abstract: Summary Background Ex vivo confocal microscopy (CM) works under two modes, fluorescence and reflectance, allowing the visualization of different structures. Fluorescence CM (FCM) requires a contrast agent and has been used for the analysis of basal cell carcinomas (BCCs) during Mohs surgery. Conversely, reflectance CM (RCM) is mostly used for in vivo diagnosis of equivocal skin tumours. Recently, a new, faster ex vivo confocal microscope has been developed which simultaneously uses both lasers (fusion mode). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
0
43
0
3
Order By: Relevance
“…In this issue of the BJD, P erez-Anker et al report their experience of using FuCM on 78 patients with BCC [60% of them showing a high-risk histological subtype (45% infiltrative, 32% nodular, 15% micronodular, 8% superficial)]. 11 With a mean time of 7 min (range 3-15) required to scan each sample, P erez-Anker et al found that FuCM is beneficial owing to the synergistic effect of visualizing both RCM and FCM features simultaneously, overcoming the individual limitations of both RCM and FCM. Overall, nuclei characteristics were better seen with the FCM and cytoplasm, and surrounding stroma were better seen with RCM.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of the BJD, P erez-Anker et al report their experience of using FuCM on 78 patients with BCC [60% of them showing a high-risk histological subtype (45% infiltrative, 32% nodular, 15% micronodular, 8% superficial)]. 11 With a mean time of 7 min (range 3-15) required to scan each sample, P erez-Anker et al found that FuCM is beneficial owing to the synergistic effect of visualizing both RCM and FCM features simultaneously, overcoming the individual limitations of both RCM and FCM. Overall, nuclei characteristics were better seen with the FCM and cytoplasm, and surrounding stroma were better seen with RCM.…”
mentioning
confidence: 99%
“…similar to polarized and non-polarized dermoscopy complementing each other). 11 The importance of the novel FuCM device is that it improves the visualization of nuclear, cytoplasmic and stromal details by simultaneously obtaining the three CM modes: RCM, FCM and FuCM. Acetic acid and acridine orange double stains may enhance different morphological features of BCC in FuCM and thus potentially aid in cancer margin assessment.…”
mentioning
confidence: 99%
See 3 more Smart Citations